APLIKASI NOTIFIKASI LOWONGAN PEKERJAAN MENGGUNAKAN JEJARING SOSIAL TWITTER (Information Technology and Telematics, 2015)
Abstract Human need for information will increase. Humans are living beings who have a desire to share with each other, via the Internet, especially social networking twitter become one of the most popular today in the world because it is considered an effective and quick to spread and convey information. The difference with the previous studies of this research is the use of twitter API and using the programming language PHP and MySQL. While the object of this study is the job vacancy notification and social networking use is twitter. Retrieving data from JobStreet job information using scraping method, the commands used in this application is using cron jobs that aims to make every 1 hour once the application automatically tweet will appear job information that is shared via twitter. The purpose of this is to make the application penetilian notifications jobs using social networking twitter using PHP and MySQL. The benefits of this research is to facilitate people in the job information that is sought through a web service.   Keywords: Notifications job, web scraping, social networking twitter, web service.